DEVICES ENSURING THE SAFETY OF OUR CHILDREN IN PASSENGER CARS - Yusupova. R. K. (Bright Mind Publishing, 2025)
This article examines the main physical and mechanical properties of a child safety device in passenger cars, as well as the classification, design features and the degree of relevance of its installation. And the level of quality of the device is determined, as well as its safety for human life.
Keywords: Bumpers, car windows and seats, interior parts of car's interior, lacquer materials, loudspeakers and shockproof shields, fuel tanks, electric jacks, electric cocks, batteries, wheels and chassis carriages, fuel pumps, generators, compressors.